Malaysian elections : time for anti-party-hopping rule? - Farish A. Noor (2012)
As Malaysia’s 13th general election draws near, there is growing concern about party-hopping by elected representatives. Malaysian civil society groups are calling for a mechanism to put an end to this undemocratic practice.